Distribution of Paron La’as As Reviewed from The Muzara’ah Contract in Pademawu Sub-District Pamekasan - Suhaimi Suhaimi; Sapto Wahyono; Mohammad Fahrur Rozi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The agricultural sector plays a crucial role in supporting the livelihoods and economic stability of Indonesian society, particularly within the Pademawu community. Indonesia’s vast agrarian landscape and strong reliance on agriculture have shaped various local traditions and cooperative systems among farmers. One such system is the muzara’ah agreement, a form of agricultural profit-sharing partnership between landowners and cultivators. This research focuses on the implementation of the Paron La’as agreement, a traditional form of muzara’ah practiced by the Pademawu community, which reflects both economic cooperation and Islamic legal principles. The study employs a qualitative approach using a field research design to collect descriptive data through interviews, observation, and documentation. The findings reveal that the Paron La’as system is conducted in accordance with the principles of Islamic law governing muzara’ah contracts, particularly in terms of fairness, mutual consent, and proportional profit distribution between landowners and farmers. Moreover, the study highlights how this cooperative practice not only strengthens economic ties within the community but also preserves local wisdom and social harmony. Therefore, the Paron La’as model demonstrates an effective integration of Islamic economic values with traditional agricultural systems, serving as a sustainable example of community-based agricultural cooperation in Indonesia.